1992
DOI: 10.1017/s0022112092000521
|View full text |Cite
|
Sign up to set email alerts
|

Field observations of orbital velocities and pressure in weakly nonlinear surface gravity waves

Abstract: Field measurements of wave orbital velocities and pressure, collected in the lower part of the water column in 7 m depth with a three-component acoustic Doppler current meter and a co-located pressure transducer, are compared to the second-order theory for weakly nonlinear surface gravity waves in arbitrary water depth (Hasselmann 1962). Pressure and velocity spectra and cross-spectra are in excellent agreement with (linear) free wave transfer functions, even at (and higher than) twice the spectral peak freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…This assumption, which implies a frictionless interior ocean, is well supported by the observed weak attenuation of swells propagating across ocean basins (Ardhuin et al 2009) and local comparisons of the observed wave orbital motion with second order wave theory (e.g. Herbers et al 1992). Vorticity effects can be important in the vicinity of the surface and bottom boundary layers (e.g.…”
Section: Equations Of Motionmentioning
confidence: 67%
“…This assumption, which implies a frictionless interior ocean, is well supported by the observed weak attenuation of swells propagating across ocean basins (Ardhuin et al 2009) and local comparisons of the observed wave orbital motion with second order wave theory (e.g. Herbers et al 1992). Vorticity effects can be important in the vicinity of the surface and bottom boundary layers (e.g.…”
Section: Equations Of Motionmentioning
confidence: 67%
“…However, in practice, this capability is compromised by the small horizontal aperture of the array and high noise levels of the ADCP velocity measurements. Highresolution estimation techniques that attempt to fit an exact or near-exact solution to (10) are known to be extremely sensitive to errors in the observations (especially for wavelengths that are long compared with the array footprint), typically resulting in estimates of S(u) with wildly spurious structures (see Herbers and Guza 1990 for further discussion and examples).…”
Section: The Directional Distributionmentioning
confidence: 99%
“…The first-generation, so-called narrowband ADCPs relied on pulse-to-pulse incoherent processing, resulting in noise levels that were too high to resolve high-frequency wind waves and swell, and thus these instruments were used primarily to observe mean current profiles based on long averaging intervals. On the other hand, pulse-to-pulse coherent systems (Lhermitte and Serafin 1984) with very low noise levels can provide accurate measurements of the wave orbital flow field (e.g., Herbers et al 1991Herbers et al , 1992 but suffer from a rangevelocity ambiguity that is undesirable for long-range current profiling applications. The second-generation of so-called broadband ADCPs combines features of incoherent and coherent sonars to reduce noise levels while maintaining the full-range profiling capability (Brumley et al 1991).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations